Direct superior approach versus posterolateral approach in total hip arthroplasty: a randomized controlled trial on early outcomes on gait, risk of fall, clinical and self-reported measurements - Michele Ulivi; Luca Orlandini; Jacopo A Vitale; Valentina Meroni; Lorenzo Prandoni; Laura Mangiavini; Nicolò Rossi; Giuseppe M Peretti (Acta Orthopaedica, 2021)
Background and purpose — Several surgical approaches are used in primary total hip arthroplasty (THA). In this randomized controlled trial we compared gait, risk of fall, self-reported and clinical measurements between subjects after direct superior approach (DSA) versus posterolateral approach (PL) for THA. Patients and methods — Participants with DSA (n = 22; age 74 [SD 8.9]) and PL (n = 23; age 72 [7.7]) underwent gait analysis, risk of fall assessment and Timed Up and Go Test (TUG) before (PRE), 1 month (T1) and 3 months after (T3) surgery. Data on bleeding and surgical time was collected. Results — DSA resulted in longer surgical times (90 [14] vs. 77 [20] min) but lower blood loss (149 [66] vs. 225 [125] mL) than PL. DSA had lower risk of fall at T3 compared with T1 and higher TUG scores at T3 compared with T1 and PRE. PL improved balance at T3 compared with T1 and PRE. Spatiotemporal gait parameters improved over time for both DSA and PL with no inter-group differences, whereas DSA, regarding hip rotation range of motion, showed lower values at T3 and T1 compared with PRE and, furthermore, this group had lower values at T1 and T3 compared with PL. All foregoing comparisons are statistically signficant (p < 0.05) Interpretation — DSA showed longer surgical time and lower blood loss compared with PL and early improvements in TUG, spatiotemporal, and kinematic gait parameters, highlighting rapid muscle strength recovery.